Utility values among glaucoma patients: an impact on the quality of life. Issue 10 (16th September 2005) - Gupta, V; Srinivasan, G; Mei, S S; Gazzard, G; Sihota, R; Kapoor, K S
Abstract : Aim: To ascertain utility values and associated quality of life with different severity and duration of glaucoma among Indian patients. Methods: Utility values of 105 consecutive patients with primary glaucoma of at least 12 months' duration were evaluated in a cross sectional study. Utility values were ascertained in five groups using both the time-trade off and standard gamble methods: group 1 (best corrected visual acuity in the better eye of 6/9 or better), group 2 (best corrected visual acuity in the better eye of 6/18 to 6/12), group 3 (best corrected visual acuity in the better eye of 6/36 to6/24), group 4 (best corrected visual acuity in the better eye of 3/60 to 6/60), and group 5 (best corrected visual acuity in the better eye of 3/60 or worse). Results: The mean utility value for the glaucoma group as a whole was 0.64 (SD 0.69; 95% confidence interval (CI), 0.58 to 0.70) with the time-trade off method and 0.86 (SD 1.00; 95% CI, 0.81 to 0.90) with the standard gamble method for a gamble of death and 0.97 (SD 1.00; 95% CI, 0.94 to 0.99) for a gamble of blindness. The mean utility results by the time-trade off method were as follows: group 1 = 0.66, group 2 = 0.66, group 3 = 0.62, group 4 = 0.55, and group 5 = 0.61. The utility value was much lower (0.46) in those with no formal education or only primary education compared to those with postgraduate education (0.75) (p = 0.038). Those patients with glaucoma of less than 5 years' duration had a utility score of 0.62 while those with glaucoma for more than 10 years had a score of 0.74 (p = 0.40). Conclusions: Visual acuity loss occurring secondary to glaucoma is associated with a substantial decrease in patient utility value (and quality of life) in a developing country like India. The utility value is directly dependent on the degree of visual acuity loss associated with the disease and educational status and not on the duration of disease, the number of medications, or the visual field indices.